Predicting Why Women Have Elective Repeat Cesarean Deliveries and Predictors of Successful Vaginal Birth After Cesarean. Issue 2 (June 2015) - Mone, F.; Harrity, C.; Toner, B.; Mcnally, A.; Adams, B.; Currie, A.
Abstract : ( Int J Gynaecol Obstet . 2014;126(1):67–69)